2013
DOI: 10.5194/npg-20-59-2013
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of asymmetries in propagating mode-2 waves

Abstract: Abstract.Using numerical simulations performed with a pseudo-spectral incompressible Navier-Stokes solver, we describe the asymmetries that arise in the recirculating core of mode-2 internal, solitary-like waves. The waves are generated in a manner consistent with many laboratory studies, namely via the collapse of a region of mixed fluid. Analysis of the simulations reveals that asymmetries across both the wave crest and the pycnocline centre develop in the spatial distribution of density, kinetic energy and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
21
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 33 publications
6
21
0
Order By: Relevance
“…Similar to the case 1, the characteristics and energy loss of the amplitude-modulated wave packet for the case 5 were also similar with the breather definition. Noted that the breather solution exist only if the cubic nonlinearity coefficients in Gardner equation is positive (Lamb et al, 2007), but the configuration of the stratification in our simulation results a negative cubic nonlinearity coefficient in Gardner equation (Grimshaw et al, 2010;Talipova et al, 2011) and it means the breather is not allowed The oscillating tail was frequently observed in similar studies (Carr et al, 2015;Olsthoorn et al, 2013;Stastna et al, 2015). Its generation was related to the shear, and the tail was sustained by continuous energy input.…”
mentioning
confidence: 62%
See 2 more Smart Citations
“…Similar to the case 1, the characteristics and energy loss of the amplitude-modulated wave packet for the case 5 were also similar with the breather definition. Noted that the breather solution exist only if the cubic nonlinearity coefficients in Gardner equation is positive (Lamb et al, 2007), but the configuration of the stratification in our simulation results a negative cubic nonlinearity coefficient in Gardner equation (Grimshaw et al, 2010;Talipova et al, 2011) and it means the breather is not allowed The oscillating tail was frequently observed in similar studies (Carr et al, 2015;Olsthoorn et al, 2013;Stastna et al, 2015). Its generation was related to the shear, and the tail was sustained by continuous energy input.…”
mentioning
confidence: 62%
“…Between 10 T and 38 T, ~20% of mode-2 ISW total energy lost,it was a 15 little smaller than the typical observation results. Relatively high energy loss rate and a large amplitude oscillating tail in the third transect of the field observations could be probably attributed to the effect of a shoaling pycnocline (Shroyer et al, 2010) and thus the enhancement of the asymmetries in stratification, which could increase the energy loss of the wave during the propagation of mode-2 ISWs (Carr et al, 2015;Olsthoorn et al, 2013). …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The dominant laboratory insights on Kelvin waves in channel geometry come from the experimental work of Maxworthy (1983) and Renouard et al (1987). These authors performed lab-scale experiments in which mode-2 (Maxworthy, 1983) and mode-1 (Renouard et al, 1987) Kelvin waves were generated in a rectangular domain.…”
Section: Introductionmentioning
confidence: 99%
“…These authors performed lab-scale experiments in which mode-2 (Maxworthy, 1983) and mode-1 (Renouard et al, 1987) Kelvin waves were generated in a rectangular domain. Both authors found that though the wave amplitude increased at the channel wall with increasing rotation rate, the phase speed and shape were comparable to waves of similar amplitude in the presence of no rotation.…”
Section: Introductionmentioning
confidence: 99%